Morphological diversity of springtails (Hexapoda: Collembola) as soil quality bioindicators in land use systems Diversidade morfológica de colêmbolos (Hexapoda: collembola) como bioindicadora de qualidade do solo em sistemas de uso - Machado J.D.S.* (2019)
© 2019, Universidade Estadual de Campinas UNICAMP. All rights reserved.The aim of this work was to evaluate the soil quality of native forest, eucalyptus plantations, pasture, integrated crop-livestock, and no-tillage systems, correlating the morphological diversity of springtails with physical and chemical soil properties. Springtail samples were captured from soils of the southern plateau of the State of Santa Catarina in Brazil, during winter and summer, by using Pitfall traps, using a 3 × 3 point grid. The morphotyping of springtails consisted of the observation of five traits and for each one a partial value of the eco-morphological index was assigned to obtain the modified Soil Quality Index. A correlation of the morphotype abundance and diversity with physical (soil moisture, bulk density, biopores, microporosity, and macroporosity) and chemical (pH in water, calcium/magnesium ratio and total organic carbon content) soil properties was studied, describing all results by variance and multivariate analyses. The springtail abundance and diversity were influenced by the different land use systems. Higher soil quality index was determined in native forest followed by eucalyptus plantations, pasture, no-tillage system and integrated crop-livestock, in the winter. Moreover, higher soil quality index was found in native forest followed by integrated crop-livestock, eucalyptus plantations, no-tillage system and pasture, in the summer. Therefore, the quality index of a soil can be evaluated by the springtail morphological traits in correlation with the physical and chemical properties such as calcium/magnesium ratio, total organic carbon contents, biopores, macroporosity, microporosity, soil moisture, bulky density and pH.